Effects of Different Water Sources on Growth Performance and Nutritional Composition of Hydroponic Maize Varieties - Boma VICTOR IRISO (Hasanuddin University, 2026)
This study assessed the influence of two sources of water on agronomic indices and nutritional values of two varieties of hydroponics maize fodder. The experiment was a 2 x 2 x 2 factorial model fitted into a completely randomized design, consisting of two sources of water (tap water and fish pond water), two varieties of maize seeds (OBA 2000 and Local white maize), and two harvesting regimes (8th and 10th day). The grains were cleaned, treated, and sprouted into hydroponics maize fodder using perforated aluminum trays of 36 cm x 45cm with a 3.5 cm depth for 10 days. All maize grains were manually irrigated using a plastic sprayer every 3 hours from 8am to 6pm each day. The results obtained revealed significant (P<0.05) effects of maize seed varieties, sources of water and harvesting regimes on the nutritional values and plant height, leaves number, leaves length, leaf width, fodder mat thickness, herbage yield and dry matter yield. OBA 2000 maize fodder exhibited higher (P<0.05) agronomic indices and nutrients than Local white maize hydroponic fodder in both tap water and fish water irrigated fodders on day 8 and 10 harvesting regimes respectively. Fish pond water irrigated fodders had higher (P<0.05) agronomic indices and nutrients than tap water irrigated fodders. Harvesting on day 10 had better (P<0.05) agronomic indices and nutrients than on day 8. Hence, OBA 2000 maize seed variety irrigated with fish pond water and harvesting on day 10 is recommended for maize hydroponic fodder production.